2007
DOI: 10.1037/0022-0167.54.2.132
|View full text |Cite
|
Sign up to set email alerts
|

The role of coping in the relationship between perceived racism and racism-related stress for Asian Americans: Gender differences.

Abstract: On the basis of stress and coping theory, the authors examined coping as a mediator of the relationship between perceptions of racism and racism-related stress with a sample of Asian American college students (N ϭ 336). Results indicated that coping mediated the relationship between racism and racism-related stress differentially by gender. The more that men perceived racism, the more likely they were to use support-seeking coping strategies that were associated with higher levels of racism-related stress. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 40 publications
7
74
2
Order By: Relevance
“…Previous research support our hypotheses accepted hypotheses studies examined coping as mediators. Liang, Alvarez, Juang, & Liang, (2007) found that coping was a mediator that was positively associated with poor mental health. Alvarez and Juang (2010) found that coping was negatively associated with psychological distress.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous research support our hypotheses accepted hypotheses studies examined coping as mediators. Liang, Alvarez, Juang, & Liang, (2007) found that coping was a mediator that was positively associated with poor mental health. Alvarez and Juang (2010) found that coping was negatively associated with psychological distress.…”
Section: Discussionmentioning
confidence: 96%
“…Coping is an adoptive function which effort to minimize problems with self and with social relations and deal with conflicts (Weiten & Lloyd, 2008). Liang, Alvarez, Juang, and Liang, (2007) found that coping work as mediator between perception of discrimination and mental health is also positively related with stress. Alvarez and Juang (2010) study demonstrated that coping strategies mediate between the relationships of discrimination decline of mental health Relationship between perceived discrimination and loneliness among transgender…”
Section: Introductionmentioning
confidence: 94%
“…This perspective is consistent with the conceptualization of racism as a chronic stressor (Clark, Anderson, Clark, & Williams, 1999), and is based on Lazarus and Folkman's (1984) stress-coping process, in which coping is theorized to act as a mediator. For example, Liang et al (2007) found that among Asian American men, perceived racism (used interchangeably with RDEs in this study) was associated with racismrelated stress through the use of support-seeking (i.e., engagement) coping, whereas the relationship between perceived racism and racism-related stress was mediated by the use of active (i.e., engagement) coping among Asian American women. Alvarez and Juang (2010) found that for Filipino American men, active coping was negatively associated with psychological distress, whereas support-seeking and avoidance coping were positively associated with psychological distress.…”
Section: Coping With Racial Discriminationmentioning
confidence: 83%
“…In contrast, studies that examined coping as a mediator (e.g., Alvarez & Juang, 2010;Liang et al, 2007) considered the stress-coping theoretical framework; the choice of coping strategy was contingent on the nature of the stressor, and the mental health outcome was dependent on the effectiveness of coping. This perspective is consistent with the conceptualization of racism as a chronic stressor (Clark, Anderson, Clark, & Williams, 1999), and is based on Lazarus and Folkman's (1984) stress-coping process, in which coping is theorized to act as a mediator.…”
Section: Coping With Racial Discriminationmentioning
confidence: 99%
See 1 more Smart Citation